Spectrum of Rheumatological Disorders: A Clinic-based Study - Ahmed, AKM Shaheen; Rahim, Muhammad Abdur; Dewan, Pratik; Haque, Hasna Fahmima; Nazim, Reshad Falah; Afroz, Farhana; Afroze, Samira Rahat; Ahmed, Jamal Uddin; Hossain, Mostaque; Hossain, Md. Delwar; et al. (Journal of Medicine, 2014)
Objectives: To assess the prevalence and distribution of rheumatic diseases at rheumatology clinic in a tertiary level hospital. Methods: This retrospective study was done at rheumatology clinic of BIRDEM from July 2009 to December 2012. Diagnoses were reached by using clinical criteria supplemented by necessary investigations. Results: Total number of patients was 772 with female predominance (F:M ratio of 1.3:1). Mean age was 46.9 (range 13-83) years. Majority (85.9%) were in 3rd to 6th decades. Degenerative diseases (49.9%) were most common, followed by inflammatory conditions (33.5%), soft tissue rheumatism (7%), metabolic bone disease (4.8%) and connective tissue diseases (2.5%). Rheumatoid arthritis (27.7%) was the most prevalent disease, followed by osteoarthritis of knees (26.2%) and lumber spines (23.4). Tendinitis, osteoporosis, fibromyalgia and systemic lupus erythematosus prevailed in 5.6%, 4.8%, 1.4% and 1.3% cases respectively. Common comorbidities were diabetes mellitus (87.9%), hypertension (22.2%), ischaemic heart disease (12.4%), dyslipidaemia (10.1%), fatty liver (7.9%), chronic kidney disease (6.9%) and hypothyroidism (4.5%). Commonly prescribed medications were non-steroidal anti-inflammatory drugs (93%), disease modifying anti-rheumatic drugs (28.9%) and prednisolone (10.6%). Physiotherapy was required in 13.3% cases. In 56.6% cases various combination of treatment was required. In 12% patients receiving methotrexate, adverse effects occurred. Conclusion: Degenerative joint and spine diseases were more common but as an individual disease rheumatoid arthritis was the most prevalent condition. DOI: http://dx.doi.org/10.3329/jom.v15i1.19855 J Medicine 2014; 15: 23-27